Determinants of Directors' Pay in Switzerland: "Optimal-Contract" versus "Fat Cat" Explanation - Katja Rost; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Director compensation has become a fashionable topic: Cross-nationally, the earnings of executives and non-executive directors have risen significantly in recent years. Academic literature offers two hypotheses for this trend, a "fat cat" and an "optimal-contract" explanation. Proponents of the "fat cat" explanation state that directors are paid too much due to their unjustified power. Proponents of the "optimal contract" hypothesis state that competition in the managerial labour market establishes an optimal compensation contract. This study contrasts both hypotheses and presents evidence that the level of directors' pay in Swiss corporations is to be explained by "optimal contracts" and by managerial power. We give evidence to which degree the two explanations are valid.
Keywords: 330; director compensation; corporate governance; "optimal-contracts"; "fat cat" explanation